2022
DOI: 10.1155/2022/4544773
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Combined with IL-15 Enhanced the Expression of NKG2D Receptor on Patient Autologous NK Cells to Inhibit Wilms’ Tumor via MAPK Signaling Pathway

Abstract: Objective. The dysfunction of immune surveillance, a hot spot in cancer research, could lead to the occurrence and development in multicancers. However, the potential mechanisms of immunity in Wilms’ tumor (WT) remain unclear on Wilms’ tumor (WT). In this study, we aim to investigate the immune cell in WT and explore the underlying treatment strategy. Method. We quantified stromal and immune scores by using ESTIMATE algorithm based on gene expression matrix of WT patients in TCGA and GEO databases. Different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…JAK/STAT Inhibitor Totally Abolished NK Expansion and Activation. IL-2 and IL-15 could stimulate several downstream signaling pathways for NK proliferation, activation, and immune functions [63][64][65][66][67]. Among these pathways, JAK/STAT pathway is important for NK cell expansion and activation [68].…”
Section: Il-2 and Il-15mentioning
confidence: 99%
“…JAK/STAT Inhibitor Totally Abolished NK Expansion and Activation. IL-2 and IL-15 could stimulate several downstream signaling pathways for NK proliferation, activation, and immune functions [63][64][65][66][67]. Among these pathways, JAK/STAT pathway is important for NK cell expansion and activation [68].…”
Section: Il-2 and Il-15mentioning
confidence: 99%
“…21,22 It was found that, on the one hand, NK cells can migrate to the tumor microenvironment under the effect of IL-15 and IL-2, improving the cytotoxicity of NK cells and the recognition of tumor cells. [23][24][25] On the other hand, NK cells have immunomodulatory potential and can secrete cytokines and chemokines IFN-γ, TNF-α, CCL5, XCL1, and granulocyte macrophage colony stimulating factor (GM-CSF) to facilitate innate and adaptive cellular antitumor responses. [26][27][28] Attracting immune cells into the tumor microenvironment, as well as the interaction between immune cells, cell relocation, and functional activation greatly affect the anti-tumor immune response.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 It was found that, on the one hand, NK cells can migrate to the tumor microenvironment under the effect of IL‐15 and IL‐2, improving the cytotoxicity of NK cells and the recognition of tumor cells. 23 , 24 , 25 On the other hand, NK cells have immunomodulatory potential and can secrete cytokines and chemokines IFN‐γ, TNF‐α, CCL5, XCL1, and granulocyte macrophage colony stimulating factor (GM‐CSF) to facilitate innate and adaptive cellular anti‐tumor responses. 26 , 27 , 28 …”
Section: Introductionmentioning
confidence: 99%